Fatal Course of Abdominal Neonatal Intestinal Fibrosarcoma - Boutillier, Béatrice; Cardoen, Liesbeth; Alison, Marianne; Berrebi, Dominique; Rosenblatt, Jonathan; Virlouvet, Anne-Laure; Michon, Jean; Soudée, Sophie; Bonnard, Arnaud (European Journal of Pediatric Surgery Reports, 2019)
Infantile fibrosarcoma (IFS) is a rare nonrhabdomyosarcoma soft tissue tumor and accounts for less than 1% of childhood cancers. Forty per cent are present at birth and only 10% of IFS occurs in the abdomen. Our case of neonatal fibrosarcoma presented as a distal small bowel stenosis complicated with meconium peritonitis. The diagnosis was by histology of the surgical resection. The diagnosis of IFS is challenging as there are no specific features of IFS on imaging. Any unexpected solid lesion should raise the suspicion of complicated bowel tumoral lesion. If a neoplastic lesion is suspected extensive, surgery may be postponed until the final diagnosis is made.
Keywords: congenital fibrosarcoma; prenatal diagnosis; MR Imaging; haemorrhagic shock; meconium peritonitis